AdhMMP8 Vector Administration in Muscle: An Alternate Strategy to Regress Hepatic Fibrosis - Jesús García-Bañuelos; Edén Oceguera-Contreras; Ana Sandoval-Rodríguez; Blanca Estela Bastidas-Ramírez; Silvia Lucano-Landeros; Daniela Gordillo-Bastidas; Belinda C. Gómez-Meda; Arturo Santos; Eira Cerda-Reyes; Juan Armendariz-Borunda (Cells, 2023)
The development of several vaccines against the SARS-CoV2 virus and their application in millions of people have shown efficacy and safety in the transfer of genes to muscle turning this tissue into a protein-producing factory. Established advanced liver fibrosis, is characterized by replacement of hepatic parenchyma by tissue scar, mostly collagen type I, with increased profibrogenic and proinflammatory molecules gene expression. Matrix metalloproteinase 8 (MMP-8) is an interstitial collagen-degrading proenzyme acting preferentially on collagen type I when activated. This study was carried out to elucidate the effect of an intramuscularly delivered adenoviral vector containing proMMP-8 gene cDNA (AdhMMP8) in male Wistar rats with experimental advanced liver fibrosis induced by thioacetamide. Therapeutic effects were monitored after 1, 2, or 3 weeks of a single dose (3 × 1011 vp/kg) of AdhMMP8. Circulating and liver concentration of MMP-8 protein remained constant; hepatic fibrosis decreased up to 48%; proinflammatory and profibrogenic genes expression diminished: TNF-α 2.28-fold, IL-1 1.95-fold, Col 1A1 4-fold, TGF-β1 3-fold and CTGF 2-fold; and antifibrogenic genes expression raised, MMP-9 2.8-fold and MMP-1 10-fold. Our data proposes that the administration of AdhMMP8 in muscle is safe and effective in achieving liver fibrosis regression at a comparable extent as when the adenoviral vector is delivered systemically to reach the liver, using a minimally invasive procedure.